Seventeen Moments of Spring - Tatyana Lioznova (1973)
Set of 6 Discs Disc 1 - Parts 1 and 2 Disc 2 - Parts 3 and 4 Disc 3 - Parts 5 and 6 Disc 4 - Parts 7 and 8 Disc 5 - Parts 9 and 10 Disc 6 - Parts11 and 12
Keywords: Drama, History, War